Archaeological and Anthropological Aspects of the Study of the Pre-Scythian Burials from the Volga-Don Interfluve - Mariya A. Balabanova; Alexander N. Dyachenko (Нижневолжский археологический вестник)
Introduction. The paper is devoted to a study of archaeological and anthropological features of the four Pre-Scythian burials from the burial grounds of the Volga-Don interfluves. Material and Methods. In the course of the study, materials from the monuments Marinovka, Kurgan, 1 burial 17 have been examined; Pervomaisky VII, kurgan 46, burial 8; Pervomaisky VIII, kurgan 5, burial 1 and Baranovka I, kurgan10, burial 11. In order to evaluate the archaeological context, a typological research method and the results of radiocarbon dating are applied; for the purpose of studying anthropological features, craniological analysis and pathological conditions analysis were conducted. Analysis and Discussion. The study of the funeral rite and the material culture grave goods of the Pre-Scythian period made it possible to attribute the three burials to the so-called “Chernogorovsky type” and one to the “Novocherkassk type”. The dates comparison obtained by the relative chronology method with radiocarbon dating showed some underestimation of the existent burials timing in absolute dates. Individual skulls features revealed heterogeneity of composition which is associated with both the previous Late Bronze Age population from this territory who practiced the crouched position of the deceased in funeral rituals, and with newcomer groups morphologically similar to the population of the Bronze Age of Southern Siberia (Karasuk) who use elongated bones practice in the funeral rite. Furthermore, a series of the skulls pathological features showed their similarity to the population of the Sauromatian-Sarmatian period who practiced nomadic lifestyle. Conclusions: The materials from the monuments of the Volga-Don interfluve described in the paper illustrate the burial traditions similarity and morphological specificity of the Pre-Scythian population from the Northern Black Sea, the Lower Don and the Ciscaucasia regions.